Proposal for a new compilation system for metal ores in economy wide material flow accounting. (29th May 2020) - West, James; Lieber, Mirko; Lutter, Stephan; Schandl, Heinz
Abstract: The authors of this article propose a major revision of the processes used for assembling the metal ores component of economy wide material flow accounts (EW‐MFA). The case for doing this is built by describing in detail important shortcomings of current metal ores reporting systems, introducing the key features of the revised system being proposed, and then illustrating the way in which the new system both solves old shortcomings and adds important new capacities. The new capacities added are of particular interest with regard to organizing the data required for a range of practical resource and environmental monitoring and management tasks, at national and smaller scale. The various components of the case for change are explained largely using illustrative examples. The direct motivations behind this work are twofold. First, the proposed system will improve the accuracy and fitness for current uses of the metal ores accounts being assembled. Second, and more importantly, the additional capabilities of the revised system as a resource and environmental management tool will make the process of assembling EW‐MFA accounts more clearly relevant to the concerns of developing countries, which are increasingly being prevailed upon to compile these accounts. In addition to the direct benefits of improved resources and environmental management that should be enabled by the revised system, it is expected that expanding the utility derived from the EW‐MFA process will provide a stronger incentive for its institutionalization and maintenance by individual nations.